Non Malefficence pada Pasien Hipertensi: Analisis Konsep - Ani Kuswati; Sidik Awaludin (Prodi Keperawatan Purwokerto, 2024)
Background: The principle of nonmaleficence (no harm) means not causing physical and psychological harm/injury to the patient. The principle of nonmaleficence means that health workers in providing health services must always have the intention of helping patients overcome their health problems. Nonmaleficence in hypertensive patients depends on how the nurse or health worker provides assistance or nursing care so as not to cause harm/danger to the patient. Objective: the concept analysis aimed to explore Non-Malefficence pada Pasien Hipertensi. Methods: This concept analysis was carried out with the help of literature about non-maleficence obtained through the Google Scholar and Preplexity databases. The keywords used are